Ulcerative colitis - Le Berre, Catherine; Honap, Sailish; Peyrin-Biroulet, Laurent (The Lancet (British edition), 2023)
Ulcerative colitis is a lifelong inflammatory disease affecting the rectum and colon to a variable extent. In 2023, the prevalence of ulcerative colitis was estimated to be 5 million cases around the world, and the incidence is increasing worldwide. Ulcerative colitis is thought to occur in people with a genetic predisposition following environmental exposures; gut epithelial barrier defects, the microbiota, and a dysregulated immune response are strongly implicated. Patients usually present with bloody diarrhoea, and the diagnosis is based on a combination of clinical, biological, endoscopic, and histological findings. The aim of medical management is, first, to induce a rapid clinical response and normalise biomarkers and, second, to maintain clinical remission and reach endoscopic normalisation to prevent long-term disability. Treatments for inducing remission include 5-aminosalicylic acid drugs and corticosteroids. Maintenance treatments include 5-aminosalicylic acid drugs, thiopurines, biologics (eg, anti-cytokines and anti-integrins), and small molecules (Janus kinase inhibitors and sphingosine-1-phosphate receptor modulators). Although the therapeutic options are expanding, 10–20% of patients still require proctocolectomy for medically refractory disease. The keys to breaking through this therapeutic ceiling might be the combination of therapeutics with precision and personalised medicine.